Predictive accuracy of static risk factors for Canadian Indigenous offenders compared to non-Indigenous offenders: implications for risk assessment scales - Perley-Robertson, Bronwen (Psychology, crime & law, 2019)
The over-representation of Indigenous offenders in Canadian prisons highlights the importance of research on the generalizability of potential static risk factors for this group. The current investigation examined whether 87 static indicators currently assessed in Canadian federal prisons were differentially present and related to outcomes (revocations, general recidivism, and violent recidivism) for Indigenous (n = 1500) and non-Indigenous (n = 6684) male federal offenders. The follow-up was eight months for revocations and five years for any/violent recidivism. Indigenous offenders scored significantly higher risk than non-Indigenous offenders on the majority of the indicators (particularly criminal history indicators). Generally, most criminal history indicators and some offence severity indicators predicted revocations, general, and violent recidivism for Indigenous offenders; however, several of the indicators had significantly lower accuracy for Indigenous offenders (particularly criminal history indicators). Overall, Indigenous offenders are a higher risk population and several static risk indicators do not perform as well for this group as for non-Indigenous offenders. Nonetheless, there were numerous static indicators that did predict outcomes for Indigenous offenders. The current findings suggest that it is possible to meaningfully assess static risk for recidivism among Indigenous offenders.